PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI KERETA API (Studi Kasus Pada Pelanggan Kereta Api Matarmaja Kelas Ekonomi Malang- Jakarta) - Akromul Ilma Wildani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research objective is to find out and analyze the effect of service quality dimensions to consumers satisfaction at Matarmaja train transportation. This research classified as explanatory research type. Purposive sampling was used with 150 Matarmaja train’s consumers as the questionnaire respondents. The questionnaire was tested first to make sure that it is valid and reliable. Five hypothesis has been compiled and tested with multiple regression analyses to find out the t analyses results. The results shows that not every service quality dimensions give positive and significant effect to consumers satisfaction. The service quality dimensions that have positive and significant effect is reliability, responsiveness, assurance, and empathy. The other dimension, tangibles, comes out as the dimension that has no positive and significant effect to consumers satisfaction. Responsiveness comes out as the dimension that has dominant effect to Matarmaja train’s consumers satisfaction. Key Words: service quality dimensions, consumers satisfaction.